Holistic Ayurvedic Approach to Post-Menopausal Atrophic Vaginitis: A Case Study on Symptomatic Relief and Tissue Rejuvenation - Dr. Paridhi Sisodiya; Prof. (Dr.) Manjusha Karkare (The Bioscan, 2026)
Atrophic vaginitis, a common condition among postmenopausal women, arises due to estrogen deficiency, leading to vaginal dryness, pain during intercourse (dyspareunia), and other discomforts. Despite its high prevalence, it is often underdiagnosed and underreported.